Induction of integration-free human-induced pluripotent stem cells under serum- and feeder-free conditions - Hamada, Atsuko; Akagi, Eri; Yamasaki, Sachiko; Nakatao, Hirotaka; Obayashi, Fumitaka; Ohtaka, Manami; Nishimura, Ken; Nakanishi, Mahito; Toratani, Shigeaki; Okamoto, Tetsuji (In vitro cellular & developmental biology. Animal, 2020)
Human-induced pluripotent stem cells (hiPSCs) have shown great potential toward practical and scientific applications. We previously reported the generation of human dental pulp stem cells using non-integrating replication-defective Sendai virus (SeVdp) vector in feeder-free culture with serum-free medium hESF9. This study describes the generation of hiPSCs from peripheral blood mononuclear cells to increase the donor population, while reducing biopsy invasiveness. From 6-d-old primary culture of peripheral blood mononuclear cells (PBMCs) with IL-2, hiPSCs were established using SeVdp(KOSM)302L with recombinant Laminin-511 E8 fragments under serum-free condition. The established PBMC-derived hiPSCs showed pluripotency and differentiation ability both in vivo and in vitro. In addition, we evaluated microarray data from PBMC- and dental pulp-derived hiPSCs. These hiPSCs will be beneficial for characterizing the molecular mechanisms of cellular differentiation and may provide useful substrates for developing cellular therapeutics.